Alarm bells ring for patient data and privacy in the covid-19 goldrush. (18th May 2020) - Cox, David
Abstract : Patient data are being used on an unprecedented scale by governments and healthcare bodies to stop the pandemic in its tracks. But what of the long term effects of accessing such sensitive information, asks David Cox